Potensi Tabir Surya Pada Berbagai Tanaman Herbal - Mikha Ayu Lia Ningsih; Mita Lianastuti; Qori Putri Suciyanti; Nia Yuniarsih (Jurnal Health Sains, 2022)
The skin is the outermost part of the body that can be exposed to direct sunlight. One of the cosmetics that can be used to protect the skin from the harmful effects of the sun is sunscreen. Herbal plants can be used as active ingredients for making sunscreen, such as Moringa leaves, soursop, basil, blackberries, and onion skin. The purpose of this study was to see the effectiveness of adding plant extracts in the sunscreen formula. The research method was carried out by literature review or literature review in research journal databases from 2012 to 2022. The results showed that there was an effect of sunscreen on plant extracts added to the sunscreen formula, testing both in-vitro using UV-Vis spectrophotometry and in vivo using test animal. Phenolic compounds such as flavonoids and tannins contained in these plants are proven to absorb UV rays.